Creating a database in FileMaker Pro 8 - Schwartz, Steven A. (Visual quickproject guide., 2005)
If you want to make a great-looking, practical database fast but don't want to get bogged down with the details, then you need a Visual QuickProject Guide! If you've never created a database before, the task can be daunting. Recognizing that you don't necessarily want or need to know about every FileMaker Pro 8 feature, this low-priced, compact guide is the quickest route to creating a functional, organized database. Whether you're a small business owner looking for a better way to track inventory and invoices, someone just looking for a streamlined way to keep track of your contacts, or your boss simply needs a a project database, this book covers the FileMaker Pro 8 basics with full-color illustrations and step-by-step instructions to help you get your project done quickly. The guide also includes a companion Web site with downloadable graphic buttons, custom forms and templates, and more.